A new dynamic model of thermal degradation of polymer binary mixes submitted through pyrolysis - Bellón-Hernández, Oscar Alexander; Riscanevo Espitia, Diana Yadith; Rodríguez Hernández, Ariel Adolfo (Ingeniería Solidaria, 2022)
This paper shows the validation process of a dynamic model proposed to represent the one-step thermal degradation reaction of individual components in polymer mixtures. It is complicated to model the process of thermal degradation of polymer mixtures inside pyrolysis reactors. Inside the MPW reactor, the distribution of polymeric components in the mixture is shuffled. It occurs high-temperature gradients, and it is difficult to achieve a uniform heat transfer. All these factors make it complicated to predict at all times in the process and each point of the material inside reactor the degradation reactions and the specific presence of hydrocarbon of interest. It is made a comparison between real data provided by TGA of binary mixes of plastic and the result of simulated thermal degradation obtained using a differential equation of the model for thermal degradation of the same plastics. The polymer used in this study were Expanded Polystyrene (EPS) and Low-Density Polyethylene (HDPE). The results of the simulation using the dynamic model proposed were compared to the thermograms of the five samples submitted to TGA tests. The simulation results showed a reasonable degree of approximation with a mean square error of less than 5%. Those results well approximate the loss of mass of the real samples submitted to TGA tests in all the temperature range of the process. Consequently, it is not necessary to segment the process into sub-ranges to look for parameters in each one of them.